2020
DOI: 10.21037/jtd.2020.02.33
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of prognosis factor in patients with non-small cell lung cancer receiving pneumonectomy

Abstract: Background: Pneumonectomy is a procedure that possesses several side effects, but is sometimes necessary in the management of non-small cell lung cancer (NSCLC). The benefits of pneumonectomy have yet to be clearly outlined. Methods: Data of 100 cases were extracted from the medical records of patients that underwent a pneumonectomy for NSCLC from January 2007 to December 2016. Primary outcomes were 5-year overall survival (OS) and 30-day mortality. Statistical comparisons were performed using the Chi-Square t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The 5-year survival rate of advanced NSCLC is 5-15% ( 15 ). As immunotherapy has made significant breakthroughs in NSCLC, the human immune system recruits and activates T cells to recognize and eliminate cancer cells ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival rate of advanced NSCLC is 5-15% ( 15 ). As immunotherapy has made significant breakthroughs in NSCLC, the human immune system recruits and activates T cells to recognize and eliminate cancer cells ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, PNs have relatively high morbidity and mortality (5.0%–10.0%) in the treatment of lung cancer ( 16 ). The operation is traumatic and the risk of postoperative complications including cardiac arrhythmias, cardiac failure, pulmonary infection, bronchopleural fistula, and acute respiratory distress syndrome (ARDS) is high ( 6 , 7 , 17 , 18 ). Complication rates are generally higher after a right PN and these may affect long-term survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, a PN remains challenging with high complications, such as bronchopleural fistula, progressive pulmonary hypertension, respiratory failure, etc. ( 6 , 7 ). Depending on the surgeon's experience, and the histological and anatomical characteristics of the lung and tumor, survival may be better for a left PN than the right ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in 2019, Yang et al reported that right-sided or left-sided pneumonectomy after induction chemotherapy was not beneficial for long-term survival ( 23 ). Wang et al also analyzed the data of 100 cases with pneumonectomy and found that the right- or left-side resection didn't give a long-term survival benefit for those patients ( 24 ). However, according to the study conducted by Dhanasopon et al, right pneumonectomy patients had worse prognosis compared to left pneumonectomy patients ( 25 ).…”
Section: Discussionmentioning
confidence: 99%